Effect of Prolonged Overdose Sorbitol and Aspartame Administration on Serum Lipid Profile: Experimental Finding (Medico Legal Update, 2021)
The aim of this study was to investigate the effect of Prolonged Overdose Sorbitol and AspartameAdministration on serum Lipid Profile levels in female Rats. Blood samples were obtained from (18) adultfemale rats that treated with (100 mg/day) of sorbitol and (18) rats that treated with of Aspartame for 30 days,as well as (18) healthy rats that were given (Normal Saline) for 30 days as a control group. They dividedinto three groups as the following: Sor Group:- Included eighteen female rats that treated with (100 g/day)of sorbitol, Asp Group:- Included eighteen female rats that treated with (100 g/day) of Aspartame controlGroup:- Included (18) healthy rats that was given (Normal Saline) for 30 days. Results: the results in thisstudy showed no significantly different (p?0.05) in (TC), (TG), (HDL), (LDL), (VLDL) levels in the treatedgroup with Asp in comparison with control group while serum (TG) and (vLDL) showed significant increase(p?0.05) in treated group with Sor in comparison with control group, also the study reveals significantincrease (p?0.05) in serum (TG) and (vLDL) in treated group with Sor in comparison with treated groupwith Asp while there were no significant different (p?0.05) in serum (TC), (HDL), levels in the group thattreated with Sor in comparison with group treated with Asp and control group. In conclusion: The use ofoverdoses than permissible of sorbitol and aspartame for a prolonged period leads to disturbance of lipidprofile levels, but it is statistically imperceptible.